Diseño y construcción de un prototipo de verificación de carga,luces y encendido de motocicletas (2020)
The diagnosis of elements of the electrical system of a motorcycle such as coils, CDI (capacitor discharge circuit) and rectifying regulators is limited, because the diagnosis is made in an empirical way, there are no trainings for the use of new equipment, adding to this the high cost of testing equipment. In this case, the impossibility of its acquisition damages customers and workshops, generating unnecessary expenses and erroneous evidence. The objective of this work is to design and build a prototype for testing ignition systems, lights and battery charging, with the help of a software called Proteus; obtaining as a result the construction of a low-cost and easy-tooperate diagnostic equipment that allows simulating electrical signals to verify rectifying regulators, CDIs, and high coils. The design and construction process is described, as well as the testing and operation of the equipment.